UNLOCKING GRAMMARLY’S POTENTIAL TO FACILITATE NOTICING AND UPTAKE IN EFL WRITING - Yuliana Angreini Syafruddin (Universitas Muhammadiyah Muara Bungo, 2026)
The research aims to show how Grammarly can be integrated into the learning process to increase the noticing and learners’ uptake of grammar and writing skills. The research used the descriptive qualitative method to understand the noticing process and analyze the learners’ uptake to understand the acquisition and learning process in depth. The study was based on the framework of Schmidt’s (1990) Noticing Hypothesis and the Learner’s Uptake Concept from Lyster and Ranta (1997). The participants in the study were a group of adults who took an IELTS class at KIES Aceh, one of the intensive learning courses in Banda Aceh, ranging from beginner to intermediate level. To receive comprehensive data, the study employed the Noticing Sheet for students to record their noticing process; then, the students’ writings were also compared to analyze the uptake. The research shows that Grammarly could facilitate the students’ noticing process when the automated feedback was used in the revision stage of the learning process. Grammarly could also help the teachers by providing constant and automated feedback for numerous students’ writings in a short period of time.